Software and intelligent sciences new transdisciplinary findings - Wang, Yingxu, 1956- (Information Science Reference, 2012)
"This book discusses the transdisciplinary field known as software and intelligence sciences covering an array of developments in computer science, theoretical software engineering, cognitive science, cognitive informatics, and intelligence science"--Vydavatelská anotace
Keywords: počítačová věda -- mezioborový kontext; software -- mezioborový kontext; softwarové inženýrství -- mezioborový kontext; umělá inteligence; computer science -- interdisciplinary context; software -- interdisciplinary context; software engineering -- interdisciplinary context; artificial intelligence; kolektivní monografie; elektronické knihy; collective monographs; electronic books